Effects of Saponins of Semen Ziziphi Spinosae on Oxidative Damage of Liver and Kidney and Intestinal Microflora in Lead-exposed Mice - Weidong CAO; Lihong LIU (Shipin gongye ke-ji)
Objective: To investigate the effects of saponins of Semen Ziziphi Spinosae (SSZS) on liver and kidney oxidative damage and intestinal flora composition in lead-exposed mice and explore its detoxification mechanism. Methods: The Pb-intoxicated mice model was induced by drinking water containing 0.05% lead acetate. Different concentrations of SSZS and DMSA were administered orally to the mice for treatment. During the experiment, the weight changes of the mice were recorded, and the Pb content of blood, liver, kidney and brain, TC and TG levels of plasma and liver, as well as oxidative stress related indicators in liver and kidney were measured. In addition, the expression of autophagy related genes in the liver and kidney was detected, and 16S rDNA sequencing technology was used to analyze changes in fecal intestinal flora of mice. Results: Compared with the Pb group, SSZS significantly reduced Pb content of the blood, liver, kidney and brain in mice, increased antioxidant enzyme activity in the liver and kidney, and improved lipid metabolism disorders caused by Pb exposure. In addition, SSZS inhibited that Pb induced excessive autophagy in liver and kidney cells by regulating the expression levels of autophagy related genes of Beclin1, LC3-Ⅱ, and Lamp2 mRNA of liver and kidney in mice, thereby reducing liver and kidney damage caused by Pb exposure. Moreover, SSES increased the richness and diversity of the fecal intestinal flora in mice, and increased the relative abundance of norank-f-Muribacaceae and Lactobacillus, decreased the relative abundance of Allobacterium, Staphylococcus, and Coriobacteriaceae-UCG-002, regulated the composition of intestinal flora in Pb-exposed mice, and improved gut health. Conclusion: SSZS can alleviate Pb poisoning in mice by regulating the composition of intestinal flora and the expression of autophagy genes in liver and kidney, increasing the antioxidant enzymes activity of liver and kidney, and improving lipid metabolism disorders caused by Pb exposure. The results of this study provides the theoretical foundation for SSZS as a natural anti-Pb agent.